Independensi Lembaga Komisi Pemberantasan Korupsi Pasca Putusan Mahkamah Konstitusi Nomor 36/Puu-Xv/2017 - Muhammad Rakha Ramadhan; Nanik Prasetyoningsih (Universitas Muhammadiyah Yogyakarta, 2024)
Fundamental changes occurred in the independent nature of the Corruption Eradication Commission (KPK) after the publication of Constitutional Court Decision Number 36/PUU-XV/2017, which before this decision was issued, the KPK was a state institution with independence in carrying out its duties and authority, namely enforcing and eradicating criminal acts. corruption, seeing that the Corruption Eradication Commission (KPK) in the Indonesian constitutional system is a state auxiliary (auxiliary state institution) with the characteristic of having independence. This legal research aims to examine the independence of the Corruption Eradication Commission (KPK) after the Constitutional Court decision Number 36/PUU-XV/2017. Explains the independence of independent state institutions in the Indonesian constitutional system, as well as the independence of the KPK institution as one of the independent state institutions following the Constitutional Court decision Number 36/PUU-XV/2017 concerning the dispute over the authority to grant the House of Representatives (DPR) questionnaire to the KPK institution. This research uses normative legal research methods which focus on positive law and legal doctrines. The types and sources of legal materials used in this research are primary legal materials, secondary legal materials, and tertiary legal materials. The technique for collecting legal materials is carried out by means of literature study, by reviewing and analyzing legal materials that are relevant to this research. The results of the research carried out by the author in this thesis are the weakening of the independence of the Corruption Eradication Commission as one of the independent auxiliary state institutions in the Indonesian constitutional system after the Constitutional Court decision Number 36/PUU-XV/2017 which decided that the DPR could use its right of inquiry. to the independent institution KPK.